2015
DOI: 10.1007/s00247-015-3514-6
|View full text |Cite
|
Sign up to set email alerts
|

Hypoplastic left heart syndrome and the nutmeg lung pattern in utero: a cause and effect relationship or prognostic indicator?

Abstract: The nutmeg lung MR appearance in HLHS fetuses is associated with increased mortality/OHT (100% in the first 5 months of life compared to 35% with HLHS alone). Not all patients with restrictive lesions develop nutmeg lung, and outcome is not as poor when restriction is present in isolation. Dedicated evaluation for nutmeg lung pattern on fetal MR studies may be useful to guide prognostication and aid clinicians in counseling parents of fetuses with HLHS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(40 citation statements)
references
References 22 publications
0
33
0
Order By: Relevance
“…For example, in the rhabdomyoma case described, dedicated fetal brain sequences revealed multiple cerebral masses, as are typically seen in tuberous sclerosis. Additional information regarding lung pathology, such as in the setting of pulmonary venous obstruction (pulmonary lymphangiectasia) or tetralogy with absent pulmonary valve (airway compression), may be very relevant in clinical decision‐making …”
Section: Complementary Diagnostic Role Of Fetal Cardiac Mrimentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in the rhabdomyoma case described, dedicated fetal brain sequences revealed multiple cerebral masses, as are typically seen in tuberous sclerosis. Additional information regarding lung pathology, such as in the setting of pulmonary venous obstruction (pulmonary lymphangiectasia) or tetralogy with absent pulmonary valve (airway compression), may be very relevant in clinical decision‐making …”
Section: Complementary Diagnostic Role Of Fetal Cardiac Mrimentioning
confidence: 99%
“…Additional information regarding lung pathology, such as in the setting of pulmonary venous obstruction (pulmonary lymphangiectasia) or tetralogy with absent pulmonary valve (airway compression), may be very relevant in clinical decision-making. [45][46][47][48][49] As yet, the prognostic value of fetal lung volume measured by MRI in conditions such as Ebstein Anomaly has not yet been proven, but with semiautomated methods to acquire these data its value may become clear.…”
Section: Complementary Diagnostic Role Of Fetal Cardiac Mrimentioning
confidence: 99%
“…87 Several studies have shown that fetal MRI provides information regarding cerebral structural findings and changes in brain metabolism in fetuses with specific CHD that may affect the postnatal prognosis. 74,75,90 In fetuses with HLHS, abnormal lung parenchyma described as "nutmeg lung" was found to be representative of abnormal pulmonary lymphatics 91 ( Figure 10). 74,75,90 In fetuses with HLHS, abnormal lung parenchyma described as "nutmeg lung" was found to be representative of abnormal pulmonary lymphatics 91 ( Figure 10).…”
Section: Fetal Magnetic Resonance Imaging (Mri)mentioning
confidence: 99%
“…74,75,90 In fetuses with HLHS, abnormal lung parenchyma described as "nutmeg lung" was found to be representative of abnormal pulmonary lymphatics 91 ( Figure 10). 90 Tetralogy of Fallot with APV fetuses with significant airway obstruction and congenital lobar emphysema is at increased risk of severe hypoxia at birth 71 ( Figure 11). 91,92 In a recent study, fetuses with HLHS and MRI findings suggesting "nutmeg lung" in the third trimester had higher mortality and higher incidence of RAS or IAS compared to the group of HLHS without these findings.…”
Section: Fetal Magnetic Resonance Imaging (Mri)mentioning
confidence: 99%
See 1 more Smart Citation